2020
DOI: 10.1029/2019tc006034
|View full text |Cite
|
Sign up to set email alerts
|

India‐Sunda Plate Motion, Crustal Deformation, and Seismic Hazard in the Indo‐Burmese Arc

Abstract: Plate motion along the Indo‐Burmese Arc (IBA), strain accommodation in the Indo‐Burmese wedge, status of active convergence and seismic vulnerability in the outer wedge, is a matter of concern due to the large population density in northeast India, Bangladesh, and Myanmar. In the present study, we have constrained the India‐Sunda plate motion by estimating the Euler pole using updated GPS observations from the region. Our estimated India‐Sunda relative plate motion at a point on the blind megathrust (24°N and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 38 publications
(82 reference statements)
2
26
2
Order By: Relevance
“…We will show later on that the shortening occurs here by seismic moment release in the IBD. This result is similar to one modelled by Panda et al 5 .
Figure 3 Changes of the modeled interseismic velocities across the Indo-Burman arc as simulated in three experiments.
…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…We will show later on that the shortening occurs here by seismic moment release in the IBD. This result is similar to one modelled by Panda et al 5 .
Figure 3 Changes of the modeled interseismic velocities across the Indo-Burman arc as simulated in three experiments.
…”
Section: Resultssupporting
confidence: 92%
“…Recent observations from the Indian, Myanmar and Bangladesh GPS networks 3 , 4 suggest that the shortening rate across the Burma plate is 12–24 mm/y and 13–17 mm/y, respectively. Based on the relative motion of India and the undeformed Sundaland block, Panda et al 5 found that convergence across the blind megathrust (~ 7 mm/y) is significantly lower than previously thought 3 , 4 . They exclude the influence of the toroidal flow from Eastern Tibet, which induces additional arc-normal motion of ~ 10 mm/y in the non-rigid Shan Plateau.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Unlike the passive seismic observations, space‐geodetic solutions provide precise control over the plate‐kinematics. Present‐day geodetic estimates show that the Indian plate converges, with respect to Sunda, toward N11°E with an estimated rate of 37 mm/yr at normal24°N and normal90°E (Mallick et al., 2019; Panda et al., 2020; Steckler et al., 2016). Initial kinematic space geodetic solutions (Vigny et al., 2003), based on a sparse and spatially restricted data set, gave indications of ample amount of IBA wedge deformation.…”
Section: Introductionmentioning
confidence: 99%